From disabling shoulder pain to full functional gain: A hectic approach for higher yield - Mondal, Samim Mahammad; Kariyappa, Mallesh; Dhar, Debjyoti; Kishore, Pratik; Yelsangikar, Kalpana (Indian Journal of Child Health, 2019)
Idiopathic brachial neuritis also known as Parsonage-Turner syndrome is a well-defined but relatively uncommon clinical entity affecting young adults. It presents with acute-onset severe shoulder pain persisting from days to weeks along with associated weakness and subsequent atrophy of muscles of the shoulder girdle, leading to marked impairment of activities of daily living. Often, the diagnosis is late and sometimes missed in the vast ocean of its mimics. We report a case of idiopathic brachial plexus neuritis in a child, who was aggressively  investigated and promptly treated very early in the course of the disease, and subsequently, muscle atrophy was prevented. This case highlights the importance of picking up the disease amid its diagnostic dilemmas and managing proactively before it evolves along its natural course which may take months to years for complete, sometimes partial recovery.